International jurisdiction of the spanish courts in international child abduction cases. The unequal treatment in similar situations - Lorente Martínez, Isabel (CUADERNOS DE DERECHO TRANSNACIONAL, 2019)
Through this interesting judgment of the Provincial Hearing of Barcelona of October 2, 2017 there is approached the study of the international jurisdiction of the Spanish courts to begin to know about a case of minors’ international kidnapping, in a case of multiple international edges, and with the movement about minor one about a not signatory country (Nigeria) of Convention of 25 October 1980 on the Civil Aspects of International Child Abduction, to Spain. Is observed the unequal treatment that can manage to have a similar case, if the movement is done of a country that is not a signatory of the Convention of 25 October 1980 to another country that yes it is.